Serum leptin levels in patients with premature ejaculation - Atmaca, M; Kuloglu, M; Tezcan, E; Semercioz, A; Ustundag, B; Ayar, A (Taylor & Francis Inc, 2002)
Leptin is a fat cell-derived hormone signaling the hypothalamus about food intake, the regulation of weight, and sexual behavior. The inhibitory effect of serotonin on libido, ejaculation, and orgasm is well documented. There is an interaction between leptinergic and serotonergic systems in the central nervous system. This study was conducted to evaluate Serum leptin levels of the patients with premature ejaculation. The study group consisted of 15 patients with premature ejaculation according to Diagnostic and Statistical Manual of Mental Disorders, Third Revised Version (DSM-III-R) and 15 healthy controls. The fasting serum leptin levels were measured. Significantly high serum leptin levels in the patients were found after body mass index or age adjustment. The intravaginal ejaculation latency time negatively correlated with leptin levels in both patient and control groups. In addition, there was a positive correlation between leptin levels and the duration of illness. It would appear that leptin may be associated with premature ejaculation.
Keywords: leptin; premature ejaculation; serotonin